2021
DOI: 10.52821/2224-5561-2021-2-169-179
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of digital training platforms of universities: domestic and foreign experience

Abstract: The purpose of the study. Assessment of the impact the COVID-19 pandemic on the quality of education based on a study of the implementation of e-learning technologies using digital platforms in both foreign and Kazakhstani universities.Methodology. Problems related to online learning and possible solutions were identified based on a retrospective and comparative analysis of foreign and Kazakhstan scientific research. Scientific literature search was carried out in large databases: Researchgate, Springer, Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…According to the Entrepreneurial Personality Concept (EPS) of Obschonka and Stuetzer (2017), entrepreneurship education should contain motivational cognitive components to improve students' entrepreneurial skills and knowledge. Research suggests that establishing an effective entrepreneurial environment fosters the growth of entrepreneurial potential and aspirations (Dinis et al, 2013;Seitbatkalova et al, 2023;Uddin et al, 2022). Additionally, Islam (2019) found that the locus of control (LOC) can influence the university environment and entrepreneurial intentions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Entrepreneurial Personality Concept (EPS) of Obschonka and Stuetzer (2017), entrepreneurship education should contain motivational cognitive components to improve students' entrepreneurial skills and knowledge. Research suggests that establishing an effective entrepreneurial environment fosters the growth of entrepreneurial potential and aspirations (Dinis et al, 2013;Seitbatkalova et al, 2023;Uddin et al, 2022). Additionally, Islam (2019) found that the locus of control (LOC) can influence the university environment and entrepreneurial intentions.…”
Section: Discussionmentioning
confidence: 99%